Ṣarfa: A Premium Kind of I‘jāz in Turāth of Al-Mu‘tazila (A Conceptual Study for An-Naẓẓām and Al-Jāḥiẓ) - Junaid Akbar; Muhammad Ikramullah (Journal of Islamic and Religious Studies, 2018)
Many theological based concepts of I‘jaz had come out in third century of Ḥijrah. One of the most popular and dynamic theories that got all scholars flabbergasted for long time was ‘ṣarfa’, which has been introduced by a well-known theologian leader of Al-Mu‘tazila; An-Naẓẓam for the first time. For him, i‘jaz of Qur’ān does not mean to be qualified with the quality of matchlessness and inimitability or having worth of being unique and exclusive in its textual phenomenon as incomparable with any other text. So from this point of view Qur’ān for him, becomes like all other holy texts and Qur’ānic text no longer remains superior to any of its sister texts. As the text of the According to him Qur’ān is no more matchless and unique to other texts so, he called it ‘ṣarfa’. People are not perfect, they make mistakes and do things against religion so, Allah Almighty dissuaded and distracted human being from bringing down any equal text, otherwise anyone could do this. The following study intends to figure out genetically all applicable and inapplicable aspects of ‘ṣarfa’ of Al-Mu‘tazila. How they have dealt and applied it? Do they agree with singular definition of ‘ṣarfa’ or do they have a mutable concept